2013
DOI: 10.1177/0300985813476061
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Enhances Mouse Lung Tumorigenesis

Abstract: The association between pulmonary inflammation and lung cancer is well-established. However, currently there are no appropriate models that recapitulate inflammation-related lung cancer in humans. In the present study, we examined, in two tumor bioassays, enhancement by bacterial lipopolysaccharide (LPS) of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)-induced lung tumorigenesis in A/J mice. Mice that were treated with NNK alone developed 29.6 ± 9.8 and 36.2 ± 4.1 lung tumors/mouse in experiment 1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 38 publications
(61 reference statements)
2
33
1
Order By: Relevance
“…In the present study, in order to develop a mouse model of inflammation-driven LSCC that closely resembles human LSCC, mice were treated with a lower dose of NTCU (about 100-fold lower than the dose used in previous studies) and a COPD-like air way inflammation was induced via repetitive exposure to LPS. Previous studies with mice have shown that LPS-induced inflammatory and pathologic changes closely mimic those observed in human COPD (35,36) and repetitive exposure of NNK-pretreated mice to LPS doubled lung tumor multiplicity, markedly increased tumor size and increased peritumoral accumulation of macrophages (37). In the present study, combinatory treatment with a lower dose of NTCU (0.5 mmol/L, about 100-fold lower than the dose used in previous studies) and LPS was as potent as or even more potent than the standard dose of NTCU (40 mmol/L) (29,30) in inducing LSCC.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, in order to develop a mouse model of inflammation-driven LSCC that closely resembles human LSCC, mice were treated with a lower dose of NTCU (about 100-fold lower than the dose used in previous studies) and a COPD-like air way inflammation was induced via repetitive exposure to LPS. Previous studies with mice have shown that LPS-induced inflammatory and pathologic changes closely mimic those observed in human COPD (35,36) and repetitive exposure of NNK-pretreated mice to LPS doubled lung tumor multiplicity, markedly increased tumor size and increased peritumoral accumulation of macrophages (37). In the present study, combinatory treatment with a lower dose of NTCU (0.5 mmol/L, about 100-fold lower than the dose used in previous studies) and LPS was as potent as or even more potent than the standard dose of NTCU (40 mmol/L) (29,30) in inducing LSCC.…”
Section: Discussionmentioning
confidence: 92%
“…However, there are several mechanisms by which the lung microbiota could contribute to lung carcinogenesis, including genotoxic pathways, bacterial metabolite effects, and induction of host inflammatory pathways (15). For example, intranasal administration of lipopolysaccharide (a membrane component of Gram-negative bacteria) in a mouse model of lung cancer significantly enhanced pulmonary inflammation and lung tumorigenesis (39). We previously showed in a human study that airway Veillonella and Streptococcus were associated with upregulation of ERK and PI3K signaling pathways in the airway, pathways regulating cell proliferation, survival, and differentiation, which are upregulated in patients with lung cancer (9).…”
Section: Discussionmentioning
confidence: 99%
“…Several findings indicate a possible role for bacteria in the promotion of lung cancer, such as the increased bacterial colonization in chronic obstructive pulmonary disease (COPD 59,60 ; which is a known risk factor for lung cancer development 61 ), a lower incidence of lung cancer in germ-free male rats, and the promotion of lung cancer by LPS or by chronic respiratory infections 24,62 . Similarly, the reduced rate of skin cancer in germ-free rats 23 and in mice lacking receptors or adaptor molecules for pro-inflammatory bacterial MAMPs 6365 also suggests a possible role for the bacterial microbiota in skin carcinogenesis.…”
Section: Cancer-modulating Effects Of Microbiotamentioning
confidence: 99%